Determination of Criteria and Drought Tolerance of Prope-Legitimate Cocoa Seed Through Polyethylene Glycol Induction - Maera Zasari; Agung Wahyu Susuilo; Ade Wachjar; Sudarsono Sudarsono (Indonesian Coffee and Cocoa Research Institute, 2020)
The availability of drought tolerant rootstock becomes one of solution to obtain tolerant cocoa clone at drought condition. The production of rootstock is easier and faster by using prope-legitimate seeds as plant materials. Seed germination selection phase can accelerate the obtainment of tolerant cocoa rootstocks. The tolerance trait of prope-legitimate seeds can be determined by seed germination on media induced by polyethylene glycol (PEG) solution. To determine the tolerant seeds, it is effective by using a specific character as selection criteria. This study aimed to obtain criteria and selection character to determine droughttolerant characteristic of prope-legitimate seed through PEG 6000 induction in the germination phase. The research was conducted at the Agronomy Laboratoryof the Indonesian Coffee and Cocoa Research Institute, Jember, East Java, Indonesia, used split plot design with five replications as experimental design. The main plot was solution of 0% and 6% PEG 6000, while the subplot were prope-legitimate seeds of 13 cocoa clones. The result showed that germination ability and sprout fresh weight were suitable as selection criteria to determine tolerant characteristic of prope-legitimate seeds to drought stress. Based on the value of tress susceptible index and clustering analysis, the tested prope-legitimate seeds were divided into three groups. The group of tolerant genotype consisted of Sca 06, while the group of medium tolerant were ICCRI 03, Sulawesi 02, KW 641, TSH 858, KEE 02, Sulawesi 03, and KW 617. The susceptible group consisted of six genotypes, namely ICS 60, KKM 22, KW 516, Sulawesi 01, and MCC 02.